Analisis Kondisi Psikologis Siswa Dalam Pembelajaran Matematika Melalui Asesmen Diagnostik - Hidayat, Yandi Wahyu; Maharani, Anggita (SJME (Supremum Journal of Mathematics Education), 2023)
This study aims to determine the psychological condition of students in learning mathematics. The psychological condition of students is important to know as a guide in preparing lesson plans. This research is a descriptive research with a quantitative approach. This study describes the results of the psychological analysis of SMA Negeri 1 Beber students which include: emotions, self-confidence, interest, and motivation. The subjects of this study were 30 students of Class XII IPS SMA Negeri 1 Beber. Based on the analysis of the results of the psychological questionnaire, it can be concluded that students' readiness in learning mathematics from the psychological aspect reaches 66% or is in the moderate category. The application of group study to the mathematics learning process can be used as an option by the teacher to be able to increase students' interest in learning. Giving project-based assignments can be given to reduce student boredom in working on math problems and to increase student experience in the learning process.